Lacunary Statistical Limit and Cluster Points of Generalized Difference Sequences of Fuzzy Numbers - Pankaj Kumar; Vijay Kumar; S. S. Bhatia (Advances in Fuzzy Systems)
The aim of present work is to introduce and study lacunary statistical limit and lacunary statistical cluster points for generalized difference sequences of fuzzy numbers. Some inclusion relations among the sets of ordinary limit points, statistical limit points, statistical cluster points, lacunary statistical limit points, and lacunary statistical cluster points for these type of sequences are obtained.